Health-related quality of life of Adolescent and Young Adult Cancer Survivors before and during the COVID-19 pandemic: longitudinal improvements on social functioning and fatigue - Carla Vlooswijk; Silvie H. M. Janssen; Lonneke V. van de Poll-Franse; Rhodé Bijlsma; Suzanne E. J. Kaal; J. Martijn Kerst; Jacqueline M. Tromp; Monique E. M. M. Bos; Roy I. Lalisang; Janine Nuver; Mathilde C. M. Kouwenhoven; Winette T. A. van der Graaf; et al. (SpringerOpen, 2023)
Abstract The health-related quality of life (HRQoL) among long-term Adolescent and Young Adult Cancer Survivors (AYACS) and an age- and sex-matched normative population was examined. Although the HRQoL of AYACS was worse compared to the normative population before and during the COVID-19 pandemic, the scores of AYACS improved over time in contrast to the normative population. Presumably, AYACS are used to adjusting their lives to stressful life events. Furthermore, the lockdown may have been beneficial for AYACS who face difficulties fully participating in society due to the impact of cancer. AYACS who encounter HRQoL issues could benefit from support interventions to empower them and build resilience.